Acurácia do teste de labirinto no rastreamento de déficits cognitivos em idosos - Silva, Marcelo Henrique Alves Ferreira da (2008)
This study intended to evaluate the maze test accuracy in cognitive deficit screening in elderly with or without neuropsychological pathology. The sample included 40 healthy young (18-25 years old; mean- 21 ± 1.6), 40 healthy old (60-77 years old; mean- 67 ± 5.1) and 18 patients with probable diagnosis of Alzheimer s disease initial stage (52-90 years old; mean- 78 ± 9.2). Data analysis was made using Anova with Tukey s post hoc, multiple linear regression analysis and ROC curve analysis. According to Tukey s test Alzheimer patients spent more time (46843 ± 37926 ms) to execute the test than healthy young (5482 ± 2873 ms; p= 0.0001) and elderly (17978 ± 13700; p= 0.0001); healthy young executed test n lower time (p= 0.035). According to the regression analysis of age, education level and cognitive performance of the three groups, the cognitive performance was the predictor of the execution time. When analyzing young and elderly only age was the predictor and the cognitive performance was the only factor to influence the test of old aged healthy and patients. The ROC curve analysis indicated 72% accuracy for young and elderly and 36% for healthy and elderly patients. The maze execution time represented a better balance between sensibility (75%) and the specificity (61%) was near 13575 ms, indicating that those subjects that execute the maze in a time higher to this value may show cognitive deficit related to the executive function. According to the results it is suggested that the maze test used in this study shows a good accuracy in the cognitive deficit tracking and may discriminate age changes